Russian aviation and air power in the twentieth century - Higham, Robin, 1925-2015.; Greenwood, John T.; Hardesty, Von, 1939- (London ; Portland, OR : Frank Cass, 1998)
"In 1977, Robin Higham and Jacob Kipp edited Soviet Aviation and Air Power, the first comprehensive study of Russian aviation. This new volume brings together both new editors and new contributors, to take a fresh look at Russian and Soviet aviation in the twentieth century." "Since the collapse of the Soviet Union in 1990, new archives have become available as well as new perspectives, and all the contributors to this new volume have based their research on newly available material. While some chapters update those in the 1977 work, most break new ground, such as those dealing with the aircraft industry, the designers, and Soviet Air combat on the periphery."--BOOK JACKET.
Introduction / Robin Higham, John T. Greenwood and Von Hardesty -- 1. Early Flight in Russia / Von Hardesty -- 2. From Chaos to the Eve of the Great Patriotic War, 1922-41 / Reina Pennington -- 3. Soviet Frontal Aviation during the Great Patriotic War, 1941-45 / John T. Greenwood -- 4. Aviation and the Transformation of Combined-Arms Warfare, 1941-45 / Tom Alison and Von Hardesty -- 5. Russian and Soviet Naval Aviation, 1908-96 / Christopher C. Lovett -- 6. The Aviation Industry, 1917-97 / John T. Greenwood -- 7. The Designers: Their Design Bureaux and Aircraft / John T. Greenwood -- 8. The Defense of Russian Aerospace / Dennis J. Marshall-Hasdell -- 9. Air Combat on the Periphery: The Soviet Air Force in Action during the Cold War, 1945-89 / Mark A. O'Neill -- 10. The Rise and Fall of Aeroflot: Civil Aviation in the Soviet Union, 1920-91 / David R. Jones -- Epilogue / Robin Higham.
Includes bibliographical references (pages 271-297) and index.
Keywords: Aeronautics -- Soviet Union -- History; Aeronautics, Military -- Soviet Union -- History; Aeronautics, Military; Soviet Union; History